The Level of Contraceptive Knowledge among Female University Undergraduates in Gitega, Burundi. A Cross-sectional Study. - Désiré Bimenyimana (Student's Journal of Health Research, 2022)
Background Modern contraceptives (MC) refer to any family planning method used to prevent pregnancy. Knowledge about fertility control is an important step towards access to and use of an appropriate contraceptive method in a timely and effective manner. In Burundi, the utilization rate among sexually active adolescents (15-19) is very low despite the reported 11% high fertility rate among these groups. Methodology A cross-sectional quantitative study was conducted among 340 female undergraduates at Gitega Universities. The study period was from June 2019 to October 2021.  The Leslie Fischer's formula was used to calculate the required sample size. A structured self-administered questionnaire consisting of 15 items was used to collect data relevant to the study. Data was entered and carried out using IBM Statistical packages for Social Science (SPSS) Statistics v23. Descriptive statistics were summarized. A Chi-square test was used to assess the association between different variables Results A total of 340 female students were studied.  68% were aged 25-29years.  The majority of the respondent 290 (85.3%) were unmarried. 198(58.2%) were single and 92(27.1%) were engaged. 41.2% were in the second year of study and 139 (40.9%) in year 3 of study.  The majority of female students (88.5%) were aware of contraceptives and the majority (67.9%) knew the correct meaning of contraception. Conclusion Despite the knowledge of modern contraceptive methods amongst female undergraduates, the utilization of modern contraception is low. The low utilization of FP may be linked to the negative perceptions and beliefs around family planning that is not well-accepted, especially among young people. Recommendations Provide high-quality contraceptive services that help female students overcome the personal and cultural barriers they face by providing care that protects their rights to voluntary, informed, and confidential contraceptive choice.